Pendampingan Pemahaman Dasar Akuntansi Keuangan Desa Pada Siswa-Siswi SMA Negeri 1 Losari Kabupaten Brebes - Mahmudah, Nurul; Faidah, Yusri Anis; Utami , Erni Unggul Sedya (Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
The aim of this community service activity is that students are able to understand the improvement of basic understanding of village financial accounting among students at SMA Negeri 1 Losari, Brebes Regency. Students are able to understand material about the basics of village financial accounting in depth so that they can practically apply it after completing their studies and are able to face every problem that exists in the village easily. This community service was carried out on Tuesday, January 16 2024, which was attended by 35 grade 11 students. The distance between the campus and the school is approximately 39.4 km using car transportation. The methods used in this community service activity include the lecture method, discussion method in delivery, apart from that, the community service team also conducted a survey directly at the location of SMA Negeri 1 Losari, Brebes Regency for initial data collection. The team also carried out observations and interviews with the school in order to find problems for this community service activity. As a result of this community service activity, students were able to understand both theoretically and in the field (Village) about village financial management obtained from the results of discussions and questions and answers.